The Legality of Automotive Drifting in the City of Bandung - Vanesya Difitri (Cinematology: Journal Anthology of Film and Television Studies, 2021)
Drifting is an automotive sport that prioritizes beauty. In drifting, driving technique is important because it not only requires high speed while on the track, but also requires good car control. Drifting is an automotive sport that has been legalized by the government, and this sport is very popular in the city of Bandung so that it can produce drifting racing stars. But with this legal and enthusiastic status, it does not guarantee that there will be adequate facilities for this drifting sport. Until finally gave birth to the Street Drifting community who channeled their drifting hobby on the streets such as Cikapundung and Pusdai roads. This raises the pros and cons. Qualitative methods with a case study approach were used to obtain various data by means of observation, interviews and documentation studies. This study found that there were illegal and legal drifting groups which resulted in the involvement of various parties such as IMI, police, traders, and local residents. The involvement of many parties occurs because 1) There are many rules and regulations for legal drifting on the circuit, 2) There are no facilities provided by the government. 3) Constraints in the economic aspects of the drivers. The implications of this research can be data in making documentary films and become knowledge for local governments to find solutions